2013
DOI: 10.1159/000354607
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities Associated with Vitiligo: A Ten-Year Retrospective Study

Abstract: Background: Vitiligo is a common disorder of depigmentation that has been associated with other autoimmune diseases. No recent large-scale data exist on the rates of comorbidities associated with vitiligo from the United States population. Objectives: To identify the prevalence of comorbidities as well as associated laboratory abnormalities in vitiligo patients. Methods: All medical records dating from January 1, 2000 to June 21, 2011 within the Research Patient Data Repository were evaluated retrospectively u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
110
2
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(141 citation statements)
references
References 18 publications
12
110
2
17
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20] There was no significant decrease in vitamin D levels in patients with associated autoimmune comorbidity in our study. Similar results have been found by Khurrum et al, Saleh et al as well as Beheshti et al 7,18,19 All other studies had found a significant decrease in vitamin D levels in patients having comorbid autoimmune conditions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20] There was no significant decrease in vitamin D levels in patients with associated autoimmune comorbidity in our study. Similar results have been found by Khurrum et al, Saleh et al as well as Beheshti et al 7,18,19 All other studies had found a significant decrease in vitamin D levels in patients having comorbid autoimmune conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Similar results were obtained in a study by Finamor et al as well as Takczi et al 9,11 However the majority of patients in other studies had a mean age below 35. [6][7][8][12][13][14][15][16][17][18][19][20] This may reflect certain social attitudes towards the disease i.e. hesitancy to consult local physicians regarding vitiligo, or presenting to a tertiary center only after prolonged native treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Однако, если сравнивать их рас-пространенность у больных РС, то она ниже, чем у больных с другими АИЗ. Так, например, распро-страненность заболеваний щитовидной железы у пациентов с витилиго по сравнению с контрольной группой составляет 21,1 и 7% соответственно (p=0,008) [7][8][9]. По мнению S. Ramagopalan и соавт.…”
Section: распространенность и структура коморбидных аиз у больных рс unclassified
“…Wartości te korelowały z czasem trwania choroby [10]. Podobne zależności dotyczyły przeciwciał przeciwjądrowych, które były obecne u 3,5-41% chorych, i czynnika reumatoidalnego stwierdzanego u 60% badanych [9,10,12,16]. Wielu pacjentów z bielactwem ma krążące cytotoksyczne przeciwciała skierowane przeciwko melanocytom oraz ich różnym komponentom, najczęściej przeciwko tyrozynazie -kluczowemu enzymowi w biosyntezie melaniny.…”
Section: Introductionunclassified
“…Częstość występowania u osób z bielactwem jednej lub kilku chorób autoimmunologicznych szacuje się na 14,4-25%, podczas gdy dla populacji ogólnej wartość ta wynosi niespełna 6% [7,9,12,16]. Ryzyko, że u pacjenta chorującego na bielactwo wystąpi inna choroba autoimmunologiczna, jest przeszło dwukrotnie większe niż w populacji ogólnej.…”
Section: Introductionunclassified